Citric Acid Promoting B Lymphocyte Differentiation and Anti-epithelial Cells Apoptosis Mediate the Protective Effects of Hermetia illucens Feed in ETEC Induced Piglets Diarrhea - Liu, Mingming; Yuan, Boyu; Jin, Xinxin; Zhu, Mingqiang; Xu, Haidong; Xie, Gaijie; Wang, Zifan; Zhang, Xue; Xu, Zhaoyun; Li, Bai; Huang, Yanhua; Lv, Yantao; et al. (Frontiers in Veterinary Science, 2021)
Newborn piglets are prone to diarrhea after weaning as a result of changes in their environment and feed. Enterotoxigenic Escherichia coli (ETEC) K88 strain is a typical pathogen that causes diarrhea in piglets. Hermetia illucens larvae are widely used in livestock and poultry production because of their high nutritional value and immunoregulatory effects. This study aimed to evaluate the protective effects of H. illucens feed in protecting against ETEC induced diarrhea in piglets and unravel the mechanisms of immune modulation and intestinal barrier maintenance. The results showed that after ETEC infection, citric acid in the serum and intestinal contents of the group fed on H. illucens larvae increased significantly, which stimulated macrophages to secrete cytokines that promote B lymphocyte differentiation, to ultimately increase the production of IgA and IgG in serum. Concomitantly, citric acid also had a positive effect on the intestinal barrier damaged due to ETEC infection by inhibiting the production of inflammatory cytokines, reducing the Bcl-2/Bax ratio, and promoting the expression of tight junction proteins. Correlation analysis showed that the increase of citric acid levels might be related to Massilia. Thus, citric acid derived from H. illucens larvae can improve the immune performance of weaned piglets and reduce ETEC-induced damage to the intestinal barrier in weaned piglets.